Understanding cultural responsive landscape of the Perak Malay Village: symbiosis of human and environment - Ismail, Nor Atiah; Nangkula, Utaberta; Mohd Yunus, Mohd Yazid; Ismail, Sumarni (American-Eurasian Network for Scientific Information, 2015)
Globally, issues of cultural and natural integration are considered as an international importance where people begin to express their concerns on the degradation of cultural landscape. The environmental convention stressed on the cultural, economic and social causes of environmental conditions and the need to look for approaches to manage environment. It is a holistic approach to landscape, which is alive to both the cultural and natural values. Therefore, it is essential to know and understand the relationship of the Malays toward their natural landscape. This paper explains Perak Malay rural house compound as a culturally responsive landscape through its planting composition. The discussion focus on the attributes of the cultural responsive landscape of Perak Malay villages and its residential compound. Understanding of this relationship will give inspiration to landscape architect or land planner to design a conducive living environment.